PENGARUH IHSG, INFLASI DAN KURS TERHADAP NILAI AKTIVA BERSIH REKSA DANA SAHAM PERIODE 2015-2019 - Laddis Aji; Taufiq Akbar (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2022)
This Purpose of research is to analyze the relationship between The Composite Stock Price Index (IHSG), Inflation and Rupiah Exchange Rate (KURS) with NAV of Stock Mutual Funds. This research used 4 samples of Stock Mutual Fund Products registered with the Financial Services Authority (OJK) during the period January 2015 – December 2019. By Purposive Sampling method obtained from the official website of the Financial Services Authority (OJK). The analysis technique used in this research is the regression of panel data. The results of the study using random effects found that the Composite Stock Price Index (IHSG) positively affect the NAV of Stock Mutual Fund while Inflation and Rupiah Exchange Rate (KURS) had no effect on the NAV Stock Mutual Fund.